Mechanical and microstructural properties of fly ash based geopolymer concrete incorporating alccofine at ambient curing. (20th August 2018) - Parveen,; Singhal, Dhirendra; Junaid, M. Talha; Jindal, Bharat Bhushan; Mehta, Ankur
Highlights: GPC is widely used in construction industry when heat curing is adopted. Fly ash alone is not able to polymerize the GPC at ambient curing. Alccofine as an additional material has been proposed. The microstructure and properties of the newly material has been studied. Conventional concrete can be replaced by GPC even at ambient curing. Abstract: In this study, the findings of the properties of fly ash based geopolymer concrete incorporating alccofine at ambient temperature, using 100% raw waste material as a binder have been reported. The fresh and hardened properties of alccofine activated geopolymer concrete like workability, water absorption, compressive, splitting tensile and flexural strengths have been studied as per Indian Standards. The prepared samples were investigated through X-ray diffraction (XRD) and Scanning electron microscope (SEM) for the determination of their phase, composition and microstructural properties. The results show that geopolymer concrete prepared with alccofine at ambient temperature not only improves the properties but also encourages to replace the conventional concrete. Furthermore, geopolymer concrete specimens prepared with alccofine emerge to ensure a densification process. The results of this study revealed that alccofine have a significant effect on the polymerization of the geopolymer concrete which in turn improves the strength and microstructural features. Also, increased molarity and fly ash content, improved the strength of all tested specimen.